Galectin-1 enhances TNFalpha-induced inflammatory responses in Sertoli cells through activation of MAPK signaling - Lei, Tao; Justus Liebig University Giessen (My University, 2018)
Gal-1 is a multifunctional lectin involved in the modulation of immune responses. Using animal models of autoimmunity and chronic inflammation Gal-1 has been shown to have anti- as well as pro-inflammatory properties. Here, a model of rat experimental autoimmune orchitis (EAO) was used to investigate the role of Gal-1 in chronic testicular inflammation. EAO is characterized by leukocytic infiltration in the interstitium, spermatogenic damage and elevated production of inflammatory mediators like TNFa and MCP-1. In normal rat testis Gal-1 is predominantly expressed in Sertoli and germ cells. In extracts from inflamed testes a significant downregulation of Gal-1 mRNA and protein expression was observed. In contrast, relative expression of Gal-1 mRNA normalized to SOX9, a Sertoli cell marker, was not significantly changed. This suggests that downregulation of Gal-1 in the EAO testis is the consequence of germ cell loss. In order to investigate an influence of Gal-1 on the immune properties of Sertoli cells, primary cells were isolated and challenged with the pro-inflammatory cytokine TNFa. Subsequently, Gal-1 expression was found to be upregulated. However, binding of the lectin SNA to Sertoli cells was increased as shown by flow cytometry. SNA is recognizing terminal a-2-6-sialic acid residues that block binding of Gal-1. In contrast, binding of L-PHA, that is recognizing ß-1-6-branching of complex N-glycans, was downregulated in TNFa challenged Sertoli cells. These findings suggest that under inflammatory conditions the glycan composition on the Sertoli cell plasma membrane becomes less favorable for Gal-1 binding so that excessive immune reactions elicited by concerted action of TNFa and Gal-1 in sterile testicular inflammations may be dampened.Gal-1 and TNFa synergistically increased expression of pro-inflammatory mediators such as MCP1, IL-1a, and IL-6 when applied to primary Sertoli cells. These effects were abrogated when Gal-1 binding was blocked by preincubation with the galactose containing disaccharide lactose. Combined stimulation of Sertoli cells with Gal-1 and TNFa lead to enhanced phosphorylation of MAP kinases p38 and JNK as compared to TNFa alone, whereas Gal-1 alone did not activate MAPK signaling. In addition, treatment of Sertoli cells with p38 and JNK inhibitors abrogated Gal-1 and TNFa induced expression of IL-1a, TNFa, IL-6 and MCP-1 mRNAs. These data show that Gal-1 enhances the pro-inflammatory activity of TNFa on Sertoli cells via stimulation of MAPK signaling.

Gal-1 ist ein multifunktionelles Lektin, das an der Modulation von Immunantworten beteiligt ist. So konnten in Tiermodellen zu Autoimmunerkrankungen und chronischen Entzündungen sowohl anti- als auch pro-inflammatorische Wirkungen von Gal-1 gezeigt werden. In dieser Arbeit wurde an einem Modell der experimentellen Autoimmun-Orchitis (EAO) in der Ratte die Rolle von Gal-1 bei chronischer testikulärer Entzündung untersucht. Die EAO ist durch Leukozyteninfiltrate im Interstitium, Schädigung der Spermatogenese und die Produktion von Entzündungsmediatoren wie TNFa und MCP-1 gekennzeichnet. In normalen Rattenhoden wurde Gal-1-Expression hauptsächlich in Sertolizellen und Keimzellen gefunden. In Extrakten aus entzündeten Hoden war die Expression von Gal-1 auf mRNA- und Proteinebene dagegen signifikant erniedrigt. Wurde die Expression von Gal-1 mRNA jedoch mit der mRNA Expression von SOX9, einem spezifischen Marker für Sertolizellen, normalisiert, dann zeigte sich die Expression im EAO-Hoden unverändert. Die verringerte Expression von Gal-1 scheint also auf den Verlust der Keimzellen im entzündeten Hoden zurück zu führen zu sein. Zur Untersuchung des Einflusses von Gal-1 auf die Immuneigenschaften von Sertolizellen wurden primäre Sertolizellen aus der Ratte verwendet, die zunächst mit dem proinflammatorischen Zytokin TNFa behandelt wurden. Dadurch wurde die Expression von Gal-1 sowie die Bindung des Lektins SNA erhöht, SNA erkennt terminale a-2-6-Sialylsäurereste, die die Bindung von Gal-1 inhibieren. Im Gegensatz dazu war die Bindung des Lektins L-PHA, das ß-1-6-Verknüpfungen in komplexem N-Glykanen erkennt, an stimulierten Sertolizellen erhöht. Unter entzündlichen Bedingungen, wie sie in sterilen testikulären Entzündungen durch die gemeinsame Wirkung von TNFa und Gal-1 ausgelöst werden können, könnte also die veränderte Zusammensetzung der Glycane auf der Oberfläche von Sertolizellen die Bindung von Gal-1 herunter regulieren, um eine überschiessende Entzündung zu verhindern. TNFa konnte die Expression pro-inflammatorischer Mediatoren wie MCP1, IL-1a und IL 6 in Sertolizellen induzieren, wobei die zusätzliche Inkubation mit Gal-1 die Wirkung von TNFa synergistisch verstärken konnte. In Anwesenheit von Laktose, einem Galaktose enthaltenden Disaccharid, konnte dieser Effekt blockiert werden. Im Vergleich zu TNFa alleine verstärkte die kombinierte Stimulation von Sertolizellen mit Gal-1 und TNFa die Phosphorylierung der MAP-Kinasen p38 und JNK, wogegen Gal-1 alleine MAPK Signalwege nicht aktivieren konnte. Darüberhinaus verhinderte die Behandlung von Sertolizellen mit p38- und JNK-Inhibitoren, die durch Gal-1 und TNFa induzierte Expression von IL-1a, TNFa, IL-6 und MCP-1 mRNA. Diese Daten zeigen also, dass Gal-1 die pro-inflammatorische Aktivität von TNFa auf Sertolizellen über die Stimulation der MAPK Signaltransduktion erhöht.
Keywords: ddc:610